What works? A review of evaluated alcohol misuse interventions among Aboriginal Australians - Gray, Dennis; Saggers, S.; Sputore, Brooke; Bourbon, D. (2000)
A study identified intervention strategies that have been effective in reducing excessive consumption of alcohol, and related harm, among some segments of Australia's Aboriginal population. It appears there is a need to employ a broader range of treatment models and complementary intervention strategies.